2023
DOI: 10.1007/s13760-023-02231-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and surgical aspects of polymorphous low-grade neuroepithelial tumor of the young (PLNTY)

Abstract: Background Polymorphous low-grade neuroepithelial tumor of the young (PLNTY) is a low-grade epilepsy-associated tumor recently introduced in WHO 2021 classification. Since it has been recognized as an independent nosological entity, PLNTY has been mainly studied from a genetic and molecular perspective, not recognizing unique characteristic clinical and radiological features. Methods A systematic literature research has been conducted aiming to identify al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…8 PLNTY is marked by genetic alterations in the MAPK pathway and features a V-Raf murine sarcoma viral oncogene homolog B1(BRAF) V600E gene mutation in 48% of cases; fibroblast growth factor receptors (FGFR) gene fusions may also be present. 9 Angiocentric glioma invariably displays MYB alterations. 2 High-grade DMGs are typified by their midline location and H3-K27 alterations, whereas DHGs are infiltrative gliomas involving the cerebral hemispheres, marked by H3-G34 mutations.…”
Section: Palavras-chavementioning
confidence: 99%
See 2 more Smart Citations
“…8 PLNTY is marked by genetic alterations in the MAPK pathway and features a V-Raf murine sarcoma viral oncogene homolog B1(BRAF) V600E gene mutation in 48% of cases; fibroblast growth factor receptors (FGFR) gene fusions may also be present. 9 Angiocentric glioma invariably displays MYB alterations. 2 High-grade DMGs are typified by their midline location and H3-K27 alterations, whereas DHGs are infiltrative gliomas involving the cerebral hemispheres, marked by H3-G34 mutations.…”
Section: Palavras-chavementioning
confidence: 99%
“…Polymorphous Low-grade Neuroepithelial Tumor of the Young (PLNTY) typically presents, in the context of epilepsy, as a well-circumscribed lesions, mainly located in the posterior inferior temporal lobe, and frequently shows dense calcification and cystic components. 9 The prominent calcification is a distinct feature, although one can also account for ganglioglioma in differential diagnosis. Angiocentric gliomas often display ill-defined margins and lack enhancement.…”
Section: Structural Imaging: Magnetic Resonance Imaging (Mri) and Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most comprehensive such study to date, conducted by Armocida et al, reviewed 51 cases in the literature and found a signi cant association between contrast enhancement and poorer seizure outcomes following surgery, but identi ed no other associations between imaging characteristics, demographic information, driver mutation, and outcomes. [9] As the BRAF V600E mutation is the most common PLNTY driver mutation identi ed in the literature, we sought to further characterize the clinical features associated with this PLNTY subtype and with clinical outcomes.…”
Section: Radiographic Characteristicsmentioning
confidence: 99%
“…Kurokawa et al was excluded for not including individual patient data[12]. A total of 23 studies were included, and an additional 3 were identi ed by reviewing the references of these articles[1]-[9],[13]-[29]. All nine cases from Johnson et al were republished in Ida et al, therefore the data from these studies was merged[2], [8].…”
mentioning
confidence: 99%